2016
DOI: 10.1159/000452533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracellular Vesicles on Neural Functional Recovery and Immunologic Suppression after Rat Cerebral Apoplexy

Abstract: Background: Previous studies have demonstrated that mesenchymal stem cells (MSCs) can promote the recovery of neural function after cerebral apoplexy by secreting multiple cytokines. In addition, cell factor-derived extracellular vesicles play an important role in recovery of neural function. The aim of this study was to determine the effect of extracellular vesicles on neural functional recovery and brain tissue remodeling after cerebral apoplexy in a rat model. Methods: The rat models with local ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Coupled to the functional recovery, more neural cells were generated in MSC-EV-treated than in control animals [ 62 , 63 , 68 ]. Comparable to the other organ systems discussed before, MSC-EV treatment reduced apoptosis rates in affected brains, but promoted angiogenesis and neurogenesis instead [ 63 , 66 , 70 , 71 , 73 , 74 ]. Both, systemic pro-inflammatory and neuro-inflammatory cues were reduced following MSC-EV treatment.…”
Section: Application Of Msc-evs In Animal Modelsmentioning
confidence: 87%
See 2 more Smart Citations
“…Coupled to the functional recovery, more neural cells were generated in MSC-EV-treated than in control animals [ 62 , 63 , 68 ]. Comparable to the other organ systems discussed before, MSC-EV treatment reduced apoptosis rates in affected brains, but promoted angiogenesis and neurogenesis instead [ 63 , 66 , 70 , 71 , 73 , 74 ]. Both, systemic pro-inflammatory and neuro-inflammatory cues were reduced following MSC-EV treatment.…”
Section: Application Of Msc-evs In Animal Modelsmentioning
confidence: 87%
“…Regarding the brain, impacts of MSC-EV treatment were mainly studied in models for ischemic stroke and traumatic brain injury (TBI) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. In addition, we studied the therapeutic effects of MSC-EVs in a rat model for inflammation-induced preterm and a sheep model for hypoxia-induced fetal brain injury [ 72 , 73 ].…”
Section: Application Of Msc-evs In Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…137,147 Both studies found equally positive therapeutic effects of MSCs and EVs. Improvement of neurological impairment, neuroprotection, and neurogenesis and angiogenesis were equally stimulated by the presence of either MSCs or EVs.…”
Section: Extracellular Vesiclesmentioning
confidence: 95%
“…135 Therefore, several studies have evaluated whether stem cell-derived EVs perform similar to MSCs in tissue regeneration in vivo. [136][137][138] The use of MSC derived EVs rather than the cells themselves may avoid possible long-term mal-differentiation of engrafted cells and attenuate many of the safety concerns related to the use of living cells.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%